Drosophila Embryonic CNS Development: Neurogenesis, Gliogenesis, Cell Fate, and Differentiation. - Crews, S.T. (Genetics, 2019)
The Drosophila embryonic central nervous system (CNS) is a complex organ consisting of ?15,000 neurons and glia that is generated in ?1 day of development. For the past 40 years, Drosophila developmental neuroscientists have described each step of CNS development in precise molecular genetic detail. This has led to an understanding of how an intricate nervous system emerges from a single cell. These studies have also provided important, new concepts in developmental biology, and provided an essential model for understanding similar processes in other organisms. In this article, the key genes that guide Drosophila CNS development and how they function is reviewed. Features of CNS development covered in this review are neurogenesis, gliogenesis, cell fate specification, and differentiation.